Implementasi Metode SAW (Simple Additive Weighting) dalam Penentuan Santri Berprestasi pada TPQ Roudhotul Jannah - Muhamad Nur Fauzan; Wardi Wardi; Anisa Dewi Zulva (International Forum of Researchers and Lecturers, 2025)
Determining outstanding students is one of the important programs at TPQ Roudhotul Jannah to give appreciation to students and motivate them to be more enthusiastic about learning. To support an objective and fair selection process, this research implemented the Simple Additive Weighting (SAW) method in determining outstanding students. The criteria used include the value of memorizing prayers and letters, attendance, discipline, morals, independence, and reading the Koran. This research shows that the SAW method is able to provide results that are structured, transparent, and in accordance with predetermined assessment standards, so that the selection process becomes more effective.